Unsteady thin film flow of a fourth grade fluid over a vertical moving and oscillating belt - Gul, T. (Elsevier Ltd, 2016)
This article studies the unsteady thin film flow of a fourth grade fluid over a moving and oscillating vertical belt. The problem is modeled in terms of non-nonlinear partial differential equations with some physical conditions. Both problems of lift and drainage are studied. Two different techniques namely the adomian decomposition method (ADM) and the optimal homotopy asymptotic method (OHAM) are used for finding the analytical solutions. These solutions are compared and found in excellent agreement. For the physical analysis of the problem, graphical results are provided and discussed for various embedded flow parameters.